The Diversity and Shared Culture of Lusheng in Guangxi: An Interethnic Symbol in Southwest China - Zhuo, Chu (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
The lusheng, a traditional Chinese bamboo wind instrument, is predominantly located in southwestern China, where ethnic minorities reside. In Guangxi, this instrument has assumed several shapes. For instance, Sanjiang possesses a six-pipe lusheng, Rongshui features a fifteen-pipe variant, and Longlin showcases enormous examples measuring six meters in height. Collectively, these encompass over 10 distinct varieties, with heights varying from 30 cm to 6 meters. The lusheng has historically evolved beyond its musical purpose to serve as a spiritual emblem for the Dong, Miao, Yao, and other ethnic communities. During events like as the Miao New Year, Slope Meetings, and the Pan Wang Festival, its booming tones reverberate through communities, functioning as ceremonial fanfares and repositories of collective memory. The performance system demonstrates extensive dimensionality. Solo compositions such as "Golden Pheasant Dance" exhibit exceptional delicacy; unison renditions by several musicians produce profound reverberations; and the most visually striking is "lusheng caitang," where hundreds of performers encircle bronze drums in coordinated choreography. The Song Dynasty "tayao" custom is entirely preserved in the Dong ethnic "Duoye" dances of Sanjiang and the Miao "Slope Meeting" festivals of Rongshui. The lusheng contains a cultural code, with tunes that express courting, recount ethnic epics, and enable competitive "sound dueling." These bamboo pipes create a nonverbal linguistic system, enhancing the instrument's significance in three ways: as a ritual tool for spiritual contact, a living historical archive, and a medium for social engagement. In 2008, Dong Ethnic Lusheng Music was inscribed on China's National Intangible Cultural Heritage List, therefore affirming its distinctive status within the nation's cultural heritage storehouse.